Effects of low energy availability on female reproductive function. (20th September 2021) - Iwasa, Takeshi; Minato, Saki; Imaizumi, Junki; Yoshida, Atsuko; Kawakita, Takako; Yoshida, Kanako; Yamamoto, Yuri
Abstract: Background: It is known that metabolic and nutritional disturbances induce reproductive dysfunction in females. The main cause of these alterations is reduced gonadotrophin‐releasing hormone (GnRH) secretion from the hypothalamus, and the underlying mechanisms have gradually been elucidated. Methods: The present review summarizes current knowledge about the effects of nutrition/metabolism on reproductive functions, especially focusing on the GnRH regulation system. Main findings: Various central and peripheral factors are involved in the regulation of GnRH secretion, and alterations in their activity combine to affect GnRH neurons. Satiety‐related factors, i.e., leptin, insulin, and alpha‐melanocyte‐stimulating hormone, directly and indirectly stimulate GnRH secretion, whereas orexigenic factors, i.e., neuropeptide Y, Agouti‐related protein, orexin, and ghrelin, attenuate GnRH secretion. In addition, kisspeptin, which is a potent positive regulator of GnRH, expression is reduced by metabolic and nutritional disturbances. Conclusion: These neuroendocrine systems may be defensive mechanisms, which help organisms to survive adverse conditions by temporarily suppressing reproduction.